Analisis Pengaruh Penambahan 10%, 15% dan 20% Flay Ash Sebagai Bahan Penambah Dalam Pembuatan Batako Menggunakan Mutu Beton K-175 Dengan Variasi Waktu 21 dan 28 Hari - Anwar, Akbar; Adjam, Idhar; Faruk, Fitriyanti; Muhammad, Amiruddin Hi. (Jurnal Ilmiah Wahana Pendidikan, 2025)
Brick is a building material component used for walls and is made simply from a mixture of Portland cement, sand and water with or without additives. In addition, the manufacture of brick also uses fly ash to improve the quality of the brick. This research was conducted at the Civil Engineering Laboratory of the University of Muhammadiyah North Maluku, the research period was 3 months from November 2024 - January 2025. The data obtained in the field and from the results of the literature are primary and secondary data as follows: 1. Primary data: Field observation data, Interview data, Sampling, Documentation data. Secondary data is data obtained indirectly at the research location which can be through raw data or references obtained from journals or supporting documents related to the research in question. The addition of 10% fly ash has a compressive strength value at the age of 21 days of concrete of 0.35 Mpa and 28 days of 0.36 Mpa. The addition of 15% fly ash has a compressive strength value at the age of 21 days of concrete of 0.29 Mpa and 28 days of 0.28 Mpa. The addition of 20% fly ash has a compressive strength value at the age of 21 days of concrete of 0.27 Mpa and 28 days of 0.21 Mpa. The results of the research conducted showed that the addition of fly ash had no effect on the manufacture of concrete blocks, because the more fly ash used, the smaller the resulting compressive strength so that it did not meet the compressive strength of concrete with K-175 quality. The addition of fly ash with a percentage of 10%, 15% and 20% did not affect the compressive strength of K-175 concrete because the average compressive strength produced at a percentage of 10%, 15% and 20% did not meet the planned compressive strength of 14.50 Mpa.